Design and Evaluation of Hazard Analysis Procedures in Mining Occupational Safety Programs - Azhari Alriza; Ardhianiswari Diah Ekawati (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Workplace accidents in the mining industry remain high, highlighting the need for systematic hazard analysis to strengthen Occupational Health and Safety (OHS) programs. This study aims to design and evaluate a Hazard Analysis Procedure (HAP) model for PT. XYZ. Using quantitative methods, the research applied the Fuzzy Delphi technique to validate OHS parameters and the Fuzzy Analytic Hierarchy Process (FAHP) to determine their relative weights. Data were obtained from ten certified OHS experts through structured questionnaires. Twenty-four indicators were identified, grouped into six main criteria: management leadership, worker participation, hazard identification and assessment, hazard prevention and control, program evaluation and improvement, and accident frequency. FAHP results showed that management commitment (0.092), hazard identification (0.088), and program evaluation (0.081) were the most influential indicators. A 95% threshold was proposed as the benchmark for successful HAP implementation. Findings provide practical recommendations and support continuous improvement of mining OHS management systems.